Vegetation Restoration Alleviated the Soil Surface Organic Carbon Redistribution in the Hillslope Scale on the Loess Plateau, China - Liang, Yipeng; Li, Xiang; Zha, Tonggang; Zhang, Xiaoxia (Frontiers in Environmental Science, 2021)
The redistribution of soil organic carbon (SOC) in response to soil erosion along the loess slope, China, plays an important role in understanding the mechanisms that underlie SOC’s spatial distribution and turnover. Consequently, SOC redistribution is key to understanding the global carbon cycle. Vegetation restoration has been identified as an effective method to alleviate soil erosion on the Loess Plateau; however, little research has addressed vegetation restoration’s effect on the SOC redistribution processes, particularly SOC’s spatial distribution and stability. This study quantified the SOC stock and pool distribution on slopes along geomorphic gradients in naturally regenerating forests (NF) and an artificial black locust plantation (BP) and used a corn field as a control (CK). The following results were obtained: 1) vegetation restoration, particularly NF, slowed the migration of SOC and reduced the heterogeneity of its distribution effectively. The topsoil SOC ratios of the sedimentary area to the stable area were 109%, 143%, and 210% for NF, BP, and CK, respectively; 2) during migration, vegetation restoration decreased the loss of labile organic carbon by alleviating the loss of dissolved organic carbon (DOC) and easily oxidized organic carbon (EOC). The DOC/SOC in the BP and NF increased significantly and was 13.14 and 17.57 times higher, respectively, than that in the CK (p < 0.05), while the EOC/SOC in the BP and NF was slightly higher than that in the CK. A relevant schematic diagram of SOC cycle patterns and redistribution along the loess slope was drawn under vegetation restoration. The results suggest that vegetation restoration in the loess slope, NF in particular, is an effective means to alleviate the redistribution and spatial heterogeneity of SOC and reduce soil erosion.